The effect of biological fertilizer application on interest amount and relative water content in rehabilitation effort of old cacao. Issue 1 (November 2021) - Palad, Marliana S.; Aminah,
Abstract: Purpose This study was to examine the effect of the application of Trichoderma asperellum and Azotobacter chroococcum on the condition of cacao leaves (RWC and LMA) and their relationship to the interest amount formed, after treatment Inarching grafting in the rehabilitation of old cacao plants from side grafting. The method used in this study was Split Plot Design, with 2 factors, namely the use of T. asperellum and A. chroococcum which were repeated 3 times each, and using Duncan's New Multiple Range Test (DNMRT). The best results obtained were the relative water content of the leaves 98.43%; LMA 225.05 mg.mm −2, which produced an average number of 62 flowers every tree, with bacteria A.chroococcum and fungus T.asperellum applied twice each using the inarching grafting method which was carried out at the time of the appearance of the flush.